(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Cultural distance is an important factor affecting tourist behaviour. This study qualitatively analyses the application of cultural distance in the tourism industry. The analysis shows that most researchers use cultural distance as an independent variable to explore the relationship between tourist behaviour, followed by the moderating variable and the dependent variable. The objective way and the subjective way (perceived cultural distance) are the main models of cultural distance measurement. International tourists and inbound and outbound tourists are the targets chosen by most researchers. This study is conducive to promoting the development of related research on cultural distance and has guiding significance for tourism managers and cultural enhancement of tourism product development.